Government procurement policy in developing countries: the case of Petrobras - Ribeiro, Cassio Garcia [UNESP]; Furtado, Andre Tosi (Sage Publications India Pvt Ltd, 2014)
The aim of this article is to discuss whether public procurement policy can promote innovation by firms located in developing countries. The literature on technological learning is used to create a typology for assessing the impact of public procurement in developing countries from the standpoint of innovation. Petrobras, a Brazilian state-owned enterprise, was chosen as a case study. Petrobras is a global leader in the field of deepwater oil production technology and so offers an interesting opportunity to investigate whether government procurement in developing countries is used to promote the capability of domestic firms to develop innovations. The article presents the findings of a field survey on P-51, a platform that was ordered by the Brazilian state-owned enterprise and began producing in 2009. The case study is based on information collected from interviews with managers of Petrobras, EPC contractors and some of the firms subcontracted to work on P-51.